2010
DOI: 10.1007/s12311-010-0220-7
|View full text |Cite
|
Sign up to set email alerts
|

An Electrophysiological Study of Visual Processing in Spinocerebellar Ataxia Type 2 (SCA2)

Abstract: Reports of visual functional impairment in spinocerebellar ataxia type 2 (SCA2) have been studied previously using pattern reversal visually evoked potentials (VEPs) with contradictory results. To provide additional evidence to this area, visual functions were studied using VEPs and event-related potentials (ERPs) in a group of ten patients with genetically verified SCA2. The electrophysiological examination included pattern reversal and motion-onset VEPs as well as visually driven oddball ERPs with an evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Out of 33 reviewed studies 16 evaluated obligatory sensory components beside the vMMN. The sensory processing was disturbed in 13 of them (Bottari et al, 2014;Cleary, Donkers, Evans, & Belger, 2013;Clery et al, 2012;Clery, Roux, et al, 2013;Fisher et al, 2010;Iijima et al, 1996;Kremlacek et al, 2011;Lorenzo-Lopez et al, 2004;Maekawa et al, 2013Maekawa et al, , 2011Stothart et al, 2014Stothart et al, , 2013, whereas deficits only in components related to processing of deviants was observed in two studies only (Tales & Butler, 2006;Urban et al, 2008). The almost ubiquitous impairment of sensory stimulus processing in reviewed studies suggests that vMMN impairment is not necessarily the only candidate marker for impairments of perceptual processes.…”
Section: Specificity To Predictive Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 33 reviewed studies 16 evaluated obligatory sensory components beside the vMMN. The sensory processing was disturbed in 13 of them (Bottari et al, 2014;Cleary, Donkers, Evans, & Belger, 2013;Clery et al, 2012;Clery, Roux, et al, 2013;Fisher et al, 2010;Iijima et al, 1996;Kremlacek et al, 2011;Lorenzo-Lopez et al, 2004;Maekawa et al, 2013Maekawa et al, , 2011Stothart et al, 2014Stothart et al, , 2013, whereas deficits only in components related to processing of deviants was observed in two studies only (Tales & Butler, 2006;Urban et al, 2008). The almost ubiquitous impairment of sensory stimulus processing in reviewed studies suggests that vMMN impairment is not necessarily the only candidate marker for impairments of perceptual processes.…”
Section: Specificity To Predictive Processingmentioning
confidence: 99%
“…Using a motion-related vMMN paradigm (in which the vMMN was calculated as an integral of the difference between the deviant minus the standard ERP within an interval 100e200 msec after stimulus onset), Kremlacek et al (2011) found generally preserved vMMN in SCA2, but also a positive correlation between the vMMN and age and age at SCA onset and a negative correlation between the vMMN and pathological load (CAG repeats e cytosineeadenineeguanine triplet coding protein ataxin-2). As highlighted by Kremlacek et al (2011), and similarly to studies of vMMN in AD, patient numbers were relatively small; a reflection of how difficult recruitment can be in such populations when rigorous inclusion and exclusion criteria are observed. However, despite these limitations, such studies show proof of concept in that such patients can be tested successfully using typical vMMN paradigms and that there is some evidence of potential abnormality in the vMMN in neurodegenerative disorders.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, these subjects show prolongation of P100 latency of visual evoked potentials [74]. Event-related evoked potentials revealed the prolongation of P300 latencies in 40% of cases with a significant correlation of this variable with the disease duration and clinical affectation [76].…”
Section: Nerve Conduction and Multimodal-evoked Potentialsmentioning
confidence: 83%